Cost and Scalability Analysis of Porcine Islet Isolation for Islet Transplantation: Comparison of Juvenile, Neonatal and Adult Pigs. Issue 7 (July 2019) - Vanderschelden, Rachel; Sathialingam, Mayilone; Alexander, Michael; Lakey, Jonathan R. T.
The limited availability of human islets has led to the examination of porcine islets as a source of clinically suitable tissue for transplantation in patients with diabetes mellitus. Islets from porcine donors are commonly used in both in vitro and in vivo experiments studying diabetes mellitus. However, there are significant differences in quality and quantity of islet yield depending on donor pig age, as well as substantial differences in the costs of pancreas procurement in adult versus neonatal and juvenile pigs. In this study, we compared the total cost per islet of juvenile pig pancreata with that of neonatal and adult pigs. Although adult porcine pancreata yield, on average, more than five times the amount of islets than do juvenile and neonatal pancreata, we found that the high price of adult pigs led to the cost per islet being more than twice that of juvenile and neonatal islets (US 0.09 vs 0.04 and 0.02, respectively). In addition, neonatal and juvenile islets are advantageous in their scalability and retention of viability after culture. Our findings indicate that isolating neonatal and juvenile porcine islets is more cost-effective and scalable than isolating adult porcine islets.